Mycobacterium tuberculosis Rv2145c Promotes Intracellular Survival by STAT3 and IL-10 Receptor Signaling - Park, Hye-Soo; Back, Yong Woo; Jang, In-Taek; Lee, Kang-In; Son, Yeo-Jin; Choi, Han-Gyu; Dang, Thi Binh; Kim, Hwa-Jung (Frontiers in Immunology, 2021)
Although Mycobacterium tuberculosis (Mtb) is an intracellular pathogen in phagocytic cells, the factors and mechanisms by which they invade and persist in host cells are still not well understood. Characterization of the bacterial proteins modulating macrophage function is essential for understanding tuberculosis pathogenesis and bacterial virulence. Here we investigated the pathogenic role of the Rv2145c protein in stimulating IL-10 production. We first found that recombinant Rv2145c stimulated bone marrow-derived macrophages (BMDMs) to secrete IL-10, IL-6 and TNF-α but not IL-12p70 and to increase the expression of surface molecules through the MAPK, NF-κB, and TLR4 pathways and enhanced STAT3 activation and the expression of IL-10 receptor in Mtb-infected BMDMs. Rv2145c significantly enhanced intracellular Mtb growth in BMDMs compared with that in untreated cells, which was abrogated by STAT3 inhibition and IL-10 receptor (IL-10R) blockade. Expression of Rv2145c in Mycobacterium smegmatis (M. smegmatis) led to STAT3-dependent IL-10 production and enhancement of intracellular growth in BMDMs. Furthermore, the clearance of Rv2145c-expressing M. smegmatis in the lungs and spleens of mice was delayed, and these effects were abrogated by administration of anti-IL-10R antibodies. Finally, all mice infected with Rv2145c-expressing M. smegmatis died, but those infected with the vector control strain did not. Our data suggest that Rv2145c plays a role in creating a favorable environment for bacterial survival by modulating host signals.